A-type doubly linked proanthocyanidin trimer and other metabolites from Canthium venosum fruits, and their biological activities. (April 2020) - Dongmo, Appolinaire Kene; Nono, Raymond Ngansop; Kaaniche, Fatma; Mawabo, Isabelle Kamga; Frese, Marcel; Chouna, Jean Rodolphe; Nkenfou, Celine Nguefeu; Lenta, Bruno Ndjakou; Ngnokam, David; Nkeng-Efouet-Alango, Pépin; Sewald, Norbert
Graphical abstract: Highlights: Monomer, dimer and trimer of catechin and epicatechin. A-type doubly linked proanthocyanidin trimer from Canthium venosum fruits. Compounds 2 and 9 exhibited good acetylcholinesterase inhibitory activity. Abstract: Phytochemical investigation of Canthium venosum fruits led to the isolation of a new doubly linked A-type proanthocyanidin trimer: epicatechin-(2 β → O →7, 4 β →8)-catechin-(5→ O →2 β, 6→4 β )-epicatechin [venosumtannin A-1 (1 )], along with twenty known compounds 2-21 . Allyl (9a ) and acetyl (9b ) derivatives of 9 were prepared. The structures of compounds were established using comprehensive spectroscopic analysis including 1D NMR, 2D NMR (COSY, HMQC, HMBC, and NOESY) and circular dichroism (CD), and by comparison with the corresponding literature data. The antioxidant, cytotoxic, acetylcholinesterase and antibacterial activities of some of the isolated compounds were investigated. In the acetylcholinesterase inhibitory activity test, compounds 2 and 9 (IC50 : 0.03 ± 1.22 × 10 −3 and 0.04 ± 1.23 × 10 −3 μ M) were more active than the references (eserine and tacrine; IC50 : 0.77 ± 1.84 × 10 −3 and 0.15 ± 1.04 × 10 −3 μM respectively).